Taxing Our Wealth - Florian Scheuer; Joel Slemrod (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper evaluates proposals for an annual wealth tax. While a dozen OECD countries levied wealth taxes in the recent past, now only three retain them, with only Switzerland raising a comparable fraction of revenue as recent proposals for a US wealth tax. Studies of these taxes sometimes, but not always, find a substantial behavioral response, including of saving, portfolio change, avoidance, and evasion, and the impact depends crucially on design features, especially the broadness of the base and enforcement provisions. Because the US proposals are very different from any previous wealth tax, experience in other countries offers only broad lessons, but we can gain insights from closely related taxes, such as the property and the estate tax, and from optimal tax analysis of the role of wealth taxation.
Keywords: 330